"I didn't want to be in charge and yet I was": Bereaved caregivers' accounts of providing home care for family members with advanced cancer. Issue 4 (1st March 2018) - Mohammed, Shan; Swami, Nadia; Pope, Ashley; Rodin, Gary; Hannon, Breffni; Nissim, Rinat; Hales, Sarah; Zimmermann, Camilla
Abstract: Objective: To describe bereaved caregivers' experiences of providing care at home for patients with advanced cancer, while interacting with home care services. Methods: Caregivers of patients who had completed a 4‐month randomized controlled trial of early palliative care versus standard oncology care were recruited 6 months to 5 years after the patient's death. All patients except one (control) had eventually received palliative care. In semi‐structured interviews, participants were asked about their experiences of caregiving. Grounded theory guided all aspects of the study. Results: Sixty‐one bereaved caregivers (30 intervention, 31 control) were interviewed, including spouses (33), adult children (19), and other family (9). There were no differences in themes between control and intervention groups. The core category of Taking charge encompassed caregivers' assumption of active roles in care, often in the face of inadequate formal support. There were 4 interrelated subcategories: (1) Navigating the system— navigating the complexities of the home care system to access resources and supports; (2) Engaging with professional caregivers— interacting with visiting personnel to advocate for consistency and quality of care; (3) Preparing for death— seeking out information about what to expect at the end of life; and (4) Managing after death— managing multiple administrative responsibilities in the emotionally charged period following death. Conclusions: Caregivers were often thrust into assuming control in order to compensate for deficiencies in formal palliative home care services. Policies, quality indicators, and guidelines are needed to ensure the provision of comprehensive, interdisciplinary home palliative care.